Sexism In Jennifer Mathieu's Moxie - Anasthasia Tiara Amanditha Polii Polii; Anik Cahyaning Rahayu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study examines the portrayal of sexism in Jennifer Mathieu’s Moxie, focusing on gender discrimination in a high school setting and the ways female characters resist inequality. Using a qualitative descriptive method and a feminist literary criticism approach, the research analyzes dialogues, narratives, and events related to sexism, verbal harassment, gender stereotypes, and women’s resistance. The analysis is based on Betty Friedan’s liberal feminism, Catharine MacKinnon’s radical feminism, and Judith Butler’s gender performativity theory. The findings reveal that sexism at East Rockport High School is reflected in verbal abuse, sexual harassment, gender stereotyping, and institutional bias that favors male students while dismissing complaints from female students. In response, the female characters challenge patriarchal norms through the Moxie movement by creating feminist zines, organizing protests, fostering female solidarity, and speaking out against injustice. The movement symbolizes courage, empowerment, and feminist awareness among young women. The study concludes that Moxie not only highlights the realities of sexism in educational settings but also emphasizes the importance of solidarity, collective action, and the courage to confront gender inequality, demonstrating that meaningful social change can begin through small but united efforts.